Soil and water conservation and management : final report (CARDI St John'sAG, 1987)
Discusses projects in three Caribbean territories designed to provide the main feature of conservation and management techniques and also to provide data-base support for the formulation and implementation of large-scale development and smaller pilot projects in natural resources conservation and management in other parts of the Caribbean. In Antigua, projects focus on conservation and utilization of water resources while in Montserrat, the projects demonstrate the use of a range of erosion control methods and structures. In Nevis, emphasis is placed on improvement of water supply. Report outlines project activities in the three territories, discusses their implementation, evaluates the results and makes recommendations.
IDS